2004
DOI: 10.1094/phyto.2004.94.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Phytophthora infestans sensu lato in Ecuador Provides New Insight Into the Origin of This Important Plant Pathogen

Abstract: The metapopulation structure of Phytophthora infestans sensu lato is genetically diverse in the highlands of Ecuador. Previous reports documented the diversity associated with four putative clonal lineages of the pathogen collected from various hosts in the genus Solanum. This paper simultaneously analyzes diversity of the complete collection of isolates, including a large number that had not yet been reported. This analysis confirmed the existence of three pathogen populations, which all appear to be clonal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
83
0
16

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 38 publications
10
83
0
16
Order By: Relevance
“…Three of these appear to be clonal lineages, each characterized by a particular mating type, mitochondrial DNA (mtDNA) haplotype, nuclear RFLP fingerprint and isoenzyme electrophoretic pattern. Each of the three lineages has been described in detail: EC-1 (Forbes et al, 1997), US-1 (Oyarzun et a1., 1998), and EC-3 (Adler et al, 2004). Another pathogen group was described as the EC-2 clonal lineage (Ordon˜ez et al, 2000) but we have since identified new genotypes of P. infestans similar to EC-2 but differing in mating type and mtDNA haplotype.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Three of these appear to be clonal lineages, each characterized by a particular mating type, mitochondrial DNA (mtDNA) haplotype, nuclear RFLP fingerprint and isoenzyme electrophoretic pattern. Each of the three lineages has been described in detail: EC-1 (Forbes et al, 1997), US-1 (Oyarzun et a1., 1998), and EC-3 (Adler et al, 2004). Another pathogen group was described as the EC-2 clonal lineage (Ordon˜ez et al, 2000) but we have since identified new genotypes of P. infestans similar to EC-2 but differing in mating type and mtDNA haplotype.…”
Section: Introductionmentioning
confidence: 91%
“…In recent studies in the tropical highlands of Ecuador we identified at least 18 host species in the Solanaceae with blight-like symptoms in nature (Adler et al, 2004). Some of the pathogen genotypes attacking these hosts are atypical and may eventually be described as one or more new species of Phytophthora (Adler et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations